Crown morphology to evaluate the growing space of four Amazon native species - Tonini, Helio; Verde, Marcelo Francia Arco (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> This work aimed at defining guidelines for thinning of four native species in pure stands, in Roraima State: Brazil nut tree (Bertholletia excelsa), Andiroba (Carapa guianensis), Ipê-roxo (Tabebuia avellanedae), and Jatobá (Hymenea courbaril). Analyses were made on the relations between main crown morphometric index, and diameter and height growth of these species. Eighty-seven trees were measured, and data taken are: diameter at breast height, total height, crown insertion height and crown diameter. Crown parameters analysis showed diameter and crown area superiority of Brazil nut, which indicates its need of a proper initial spacing and bigger growing space. However, Brazil nut crown was less efficient to maintain the same mean annual diameter increment.